Neuroactive steroids, their precursors and polar conjugates during parturition and postpartum in maternal blood: 2. Time profiles of pregnanolone isomers - Hill, M; Bicíková, M; Parízek, A; Havlíková, H; Klak, J; Fajt, T; Meloun, M; Cibula, D; Cegan, A; Sulcová, J; Hampl, R; Stárka, L (The Journal of steroid biochemistry and molecular biology, 2001)
Time profiles of the pregnanolone isomers epipregnanolone (3 beta-hydroxy-5 beta-pregnan-20-one), allopregnanolone (3 alpha-hydroxy-5 alpha-pregnan-20-one), pregnanolone (3 alpha-hydroxy-5 beta-pregnan-20-one), and isopregnanolone (3 beta-hydroxy-5 alpha-pregnan-20-one) were measured around parturition and in the postpartum period in the serum of 13 and three women with subarachnoidal and epidural analgesia, respectively. In addition, the levels of polar conjugates of all pregnanolone isomers were followed during parturition. GC/MS analysis was used for the measurement of steroid levels. Changes in concentrations of free steroids exhibited a similar pattern, with a fall primarily within the first hour after delivery. The decrease in conjugated steroids was shifted to the interval within the first hour and first day after delivery, and the changes were more pronounced. The time profile of the conjugated/free steroid ratio exhibited a significant decrease within the first hour and the first day after delivery in all of the isomers investigated. A decrease was also observed in the ratio of 3 alpha/3 beta-isomers and 5 alpha/5 beta-isomers around parturition. The possible physiological consequences of the findings are indicated.
Keywords: porodní děj; Steroids; pregnanolon; Pregnanolone; analgetika; Pregnancy; těhotenství; plynová chromatografie s hmotnostně spektrometrickou detekcí; Adult; dospělí; Labor, Obstetric; Gas Chromatography-Mass Spectrometry; Time Factors; Postpartum Period; stereoizomerie; lidé; ženské pohlaví; Humans; časové faktory; poporodní období; Analgesics; steroidy; Female; Stereoisomerism